Individual physical activity preferences of adolescents in the Czech Republic and Poland: a 14-year comparative study reflecting the gender trends and prospective responses to global lifestyle challenges - Michal Kudlacek; Karel Fromel; Dorota Groffik; Josef Mitas (BMC Pediatrics)
Abstract Background The global decline in physical activity (PA) among the youth has been exacerbated by the pandemic’s impact on their lifestyles. Addressing these adverse effects post-pandemic by supporting preferred physical activities among young individuals is crucial. The aim of the study is to investigate and compare the long-term trends in PA preferences among individuals in Poland and the Czech Republic, exploring the impact of global lifestyle challenges over the past 14 years, including the pandemic, on PA behaviors and choices. Methods The study design is cross-sectional and data gathering was in the period between 2007 and 2020, this research encompassed 19,235 participants aged 15 to 26. PA preferences were gauged using the Questionnaire on Physical Activity Preferences, while actual PA levels were measured through the International Physical Activity Questionnaire-Long Form. Crossing table, Kruskal-Wallis ANOVA, binary logistic regression and effect size coefficients were conducted. Results Among the participants, individual physical activities were favoured by 24% of Czech and 25% of Polish boys, and 23% of Czech and 25% of Polish girls. A positive correlation was found between the preference for running and higher levels of recreational, vigorous, and overall weekly PA. Additionally, an increased preference for running was associated with a higher likelihood of meeting weekly PA recommendations for both girls (OR = 1.82, CI = 1.62–2.04, p < 0.001) and boys (OR = 1.61, CI = 1.44–1.82, p < 0.001) in both countries. Conclusions Over a 14-year period, swimming, cycling, and running emerged as the most preferred PA across both Czech and Polish youth, with a notable increase in running, especially among Czech boys. Polish boys and girls also showed a growing preference for running, while Polish girls demonstrated a notable increase in badminton and ice-skating. The preference for running was associated with a higher likelihood of meeting PA recommendations, especially among Polish boys and Czech girls. Notably, activities like running, swimming, and cycling exhibited resilience to both pandemic-related restrictions and broader global lifestyle challenges, underscoring the importance of long-term monitoring of PA preferences for effective health promotion.